Influence of surgical ultrasound used in the detachment of flaps, osteotomy and odontosection in lower third molar surgeries. A prospective, randomized, and split-mouth clinical study - Silva, Leonardo de Freitas [UNESP]; Ribeiro de Carvalho Reis, Erik Neiva [UNESP]; Bonardi, Joao Paulo [UNESP]; Lima, Valthierre Nunes de [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Ponzoni, Daniela [UNESP] (Medicina Oral S L, 2020)
Background: As third molar surgery is the most commonly procedure performed in Dentistry and has been accompanied by serious postoperative disorders such as pain edema and trismus, the study aimed to evaluate if ultrasound device would be able to reduce such postoperative features. The aim of this study was to assess the effects of soft tissue flap elevation, osteotomy and odontosection using piezosurgery versus conventional technique in mandibular third molar extractions. Material and Methods: Twenty patients with impacted mandibular third molars underwent tooth extractions using two different methods. Ten patients were included in the Piezo Flap Group (PFG - the flap was elevated using piezosurgery) and ten patients were part of the Piezo Ostectomy Group (POG - osteotomy and odontosection were carried out with ultrasound tips). The contralateral tooth was included in the Control Group (CG - conventional technique). The patients were evaluated at postoperative periods of 1, 3. 7 and 14-days. The measured parameters were duration of surgery. pain trismus and swelling. Results: The mean duration of surgery for the PFG was 17.21 minutes (CG 10.07 minutes) and POG was 40.09 minutes (CG 15.97 minutes). There was no statistically significant difference in pain and trismus for any of the postoperative periods evaluated in PFG and POG (p>0.05). There was a statistically significant difference in swelling between the PFG and POG, presenting less swelling at the 3-day postoperative period (p=0.038; p<0,05). However. for the remaining analyzed periods there was no difference (p>0.05). Conclusions: Piezosurgery for tissue elevation of the surgical flap, osteotomy and dental sectioning in mandibular third molar extraction surgery promoted less edema in the early postoperative stages in mandibular third molar extractions despite the longer surgical duration.
Keywords: Third molar; piezosurgery; flap; exodontia; ostectomy